Dead‐time compensation of constrained linear systems with bounded disturbances: output feedback case. Issue 1 (1st January 2013) - Santos, Tito L. M.; Limon, Daniel; Normey‐Rico, Julio E.; Raffo, Guilherme V.
Abstract : This study presents an analysis about state estimation and dead‐time compensation effect over constrained control systems with bounded disturbances and dead‐time. It is shown that input‐to‐state stability and constraint satisfaction can be guaranteed by using an equivalent dead‐time free system with measurable states and modified disturbances. This result may be useful to simplify synthesis and analysis of a given constrained control strategy. A linear output feedback control scheme and a tube‐based model predictive control strategy are used as motivating examples.